2009
DOI: 10.1007/s10508-009-9535-1
|View full text |Cite
|
Sign up to set email alerts
|

The DSM Diagnostic Criteria for Female Sexual Arousal Disorder

Abstract: This article reviews and critiques the DSM-IV-TR diagnostic criteria for Female Sexual Arousal Disorder (FSAD). An overview of how the diagnostic criteria for FSAD have evolved over previous editions of the DSM is presented and research on prevalence and etiology of FSAD is briefly reviewed. Problems with the essential feature of the DSM-IV-TR diagnosis--"an inability to attain, or to maintain…an adequate lubrication-swelling response of sexual excitement"--are identified. The significant overlap between "arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(106 citation statements)
references
References 92 publications
(128 reference statements)
2
96
1
3
Order By: Relevance
“…Most women do not differentiate between desire and arousal (Brotto, 2010a;Brotto, Heiman, & Tolman, 2009;Graham, 2010) and there is a high comorbidity between Female Sexual Arousal Disorder (FSAD) and Hypoactive Sexual Desire Disorder (HSDD) (Basson et al, 2003b;Laumann, Paik, & Rosen, 1999). According to Hartmann, Heiser, Ruffer-Hesse, and Kloth (2002), new classification systems for female sexual problems should consider this overlap.…”
Section: Introductionmentioning
confidence: 99%
“…Most women do not differentiate between desire and arousal (Brotto, 2010a;Brotto, Heiman, & Tolman, 2009;Graham, 2010) and there is a high comorbidity between Female Sexual Arousal Disorder (FSAD) and Hypoactive Sexual Desire Disorder (HSDD) (Basson et al, 2003b;Laumann, Paik, & Rosen, 1999). According to Hartmann, Heiser, Ruffer-Hesse, and Kloth (2002), new classification systems for female sexual problems should consider this overlap.…”
Section: Introductionmentioning
confidence: 99%
“…Arguably, one of the major changes that the DSM-5 introduces to the classification of sexual dysfunctions is the merger of sexual disorders of desire and arousal in females. Researchers who advocated this amalgamation [12] based their recommendations on a large body of research suggesting that the separation may have been artificial. In addition to the increased rejection of a linear model of sexual arousal [8,9], a high comorbidity of disorders of desire and arousal was demonstrated in both men and women [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally some women may engage in sexual activity for nonsexual reasons (without any initial direct sexual desire) such as desire of emotional closeness with their partner which may then be followed by increased desire for sexual encounter if incentives of sexual activity prove to be arousing. This increased desire following sexual arousal was termed as "responsive sexual desire" (16,20). It is also suggested that decrease in desire in HSDD should not be due to adaptive reasons such as discrepancy in sexual interest between partners and/or due to relationship problems.…”
Section: Diagnostic Criteria For Substance-induced Sexual Dysfunctionmentioning
confidence: 99%
“…The current DSM IV TR definition on female sexual arousal disorder (FSAD) is based mainly on physiological criteria but research literature shows consistently low correlation between subjective reports of arousal and objective physiological changes that occur (21,22). The high overlap of different components of desire and arousal in women, the fact that low sexual arousal often coexist with complaints of low libido and treatment research data supporting that transdermal testosterone used for treatment of HSDD improved not only the desire but also arousal are some of the reasons that led authorities to further recommend merging desire and arousal diagnosis into one single entity called Female Sexual Interest and Arousal Disorder (FSIAD) where a certain amount of a total number of criteria are needed to be met in order to fulfill diagnostic criteria, should be adopted in DSM5 (20,23). Although the idea of merging the two disorders together is still mainly based on clinical judgement rather than sufficient empirical evidence, the suggestion has been welcomed by many professionals and is regarded as one of the most important propositions to be considered in DSM 5.…”
Section: Diagnostic Criteria For Substance-induced Sexual Dysfunctionmentioning
confidence: 99%